Detectability of small blood vessels and flat boundaries of soft tissues in the ultrasonic pulse echo method - L. FILIPCZYŃSKI (Archives of Acoustics)
The detectability of a small blood vessel of a radius 0.1 mm by the pulse echo ultrasonic method using a frequency of 2.5 MHz was estimated. It was assumed that the vessel was surrounded by a homogeneous soft tissue (i.e. causing no reflection) and was in the near region of the far field radiated in a continuous manner by a plane transducer of a diameter of 2 cm. The soft tissue and the walls of the vessel were assumed to have the same elastic properties as those of a liquid. The measurements were carried out in a plane polar coordinate system, where the incident wave, the reflected wave and the wave penetrating into the vessel were expressed in terms of Bessel and HankeI functions. The boundary conditions were assumed in the form of the equality of the acoustic pressures and the normal components of acoustic velocitits on each side of the surface of the vessel. Thence the magnitude of the reflected wave was determined. The losses of the signal due to the reflection of the wave, its divergence and absorption, are shown in the form of a graph from which it can be seen that the signal from the vessel considered is essentially detectible, although it lies near the noise level, and is critically dependent on the distance from the transducer due to attenuation in the tissues penetrated. The detectability of the plane boundaries of soft tissues was also determined, indicating that at a distance of 20 cm from the transducer a difference in the characteristic acoustic impedance of the tissues of 0.2% is sufficient to give a detectable echo.